1995
DOI: 10.1002/mrdd.1410010206
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐behavioral diagnosis and treatment of self‐injury

Abstract: Self-injurious behavior (SIB) in individuals with mental retardation is a severe behavioral disorder that has significant social and medical consequences. Although considerable research evidence indicates that SIB can be maintained by either environmental contingencies or biologic conditions, integrative diagnostic and treatment models have yet t o be developed. We have piloted a bio-behavioral diagnostic and treatment model t o classify and subtype cases of SIB, leading t o the selection of specific behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 28 publications
(10 reference statements)
2
36
0
Order By: Relevance
“…These results suggest two outcomes. First, the participant’s SIB was not clearly influenced by a specific environmental context; a finding that is in accordance with SIB associated with other genetic conditions (Mace and Mauk 1995). Second, the lower levels of SIB observed in the presence of alternative stimuli indicated that the provision of alternative sources of stimulation (i.e., access to toys, interaction with a clinician) would reduce the occurrence of SIB.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…These results suggest two outcomes. First, the participant’s SIB was not clearly influenced by a specific environmental context; a finding that is in accordance with SIB associated with other genetic conditions (Mace and Mauk 1995). Second, the lower levels of SIB observed in the presence of alternative stimuli indicated that the provision of alternative sources of stimulation (i.e., access to toys, interaction with a clinician) would reduce the occurrence of SIB.…”
Section: Resultssupporting
confidence: 71%
“…Mace and Mauk (1995) described a bio-behavioral model of SIB, the logic of which was applied to the interpretation of the current functional analysis results. Specifically, Mace and Mauk suggested that patterns of responding during functional analysis could be categorized along three dimensions: operant, biological, or mixed.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have found identical results in naturalistic home settings when an individual is challenged with the presentation of a stressor, e.g., removal of a protective helmet (Barrera, 2005). With regard to our population, we suspect that similar physiological precursors and processes would be found in what Mace and Mauk (1999) have subtyped as 'possibly biologic SIB.' Whether the same physiological mechanisms would be found in genetically linked SIB phenotypes (e.g., Nyhan, 2002) or in SIB topographies that have a pure self-stimulatory or sensory drive (Holburn, 1986), needs to be determined by future research.…”
Section: Discussionmentioning
confidence: 93%
“…Functional and psychiatric classification systems and their respective treatment modalities represent different and seemingly competing approaches, but there is recognition that these approaches can be combined in a complementary fashion [69][70][71][72][73]. The Neurobehavioral Model [69,73] suggests a more complete account of SIB requires consideration of environmental and biological variables.…”
Section: Integrating Behavioral Treatment With Medicationmentioning
confidence: 99%